Penerapan Pemahaman Tajwid Dengan Baik Dan Benar Di Desa Tanggalrejo Mojoagung Jombang - nasirudin, mohamad; Ashar, Salim; Aghni Akbar Hidayat, Muhammad; Robihah, Ismi; Effendi, Akmal Hidayat; Khasanah, Siti Nikmatun (Jumat Keagamaan: Jurnal Pengabdian Masyarakat, 2023)
Tanggalrejo Village is a village in Mojoagung District, Jombang Regency, East Java Province. In religious learning, especially in the field of Tajweed, the children in the village still cannot understand Tajweed science well. From here we have the idea to apply the understanding of Tajwid properly and correctly in Daterejo Village, Mojoagung District. By using the Practical Tajwid Guidebook. Method The approach taken for community service in Daterejo village is by using the Service Learning (SL) method. In implementing this activity, there are several factors that influence the increasing understanding of Tajweed for TPQ teachers and students, including the effective use of learning methods by teachers, good classroom management, providing motivation to teachers and students regarding the importance of learning Tajweed so they can read. Al-Qur'an properly and correctly, and with the Practical Tajwid Guidebook which is very easy to understand for TPQ teachers and students, in this Practical Tajwid Guidebook there is an explanation of the Tajwid laws along with examples which are directly taken from the Al-Qur'an. 'an